(untitled) (Bangladesh Journal of Anatomy, 2010)
Context: Standardization of heart morphometry in Bangladeshi Bangali population might help for the proper choice for surgical intervention and prosthetic replacement in cardiac surgery. Having this context in mind the study was carried out on hearts of adult Bangali male people. Study design: A descriptive type of study Place and period of study: Department of Anatomy, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, from February 1999 to May 1999. Materials: Thirty seven (37) apparently normal postmortem hearts of adult Bangladeshi Bangali males, collected from the morgue of Department of Forensic Medicine, Dhaka Medical College, Dhaka. Method: Age of the subject was noted from the concerned department. Length of the deceased was measured with a measuring tape from the level of vertex to the outer border of heel. Length (from apex to base) and breadth (at broadest diameter) of the heart were measured with slide calipers. Weight was measured with weighing machine. Result: The length of the hearts varied from 9.38 to 12.30 cm with mean value 11.10 (+ 0.46) cm. Breadth varied from 6.81 to 11.50 cm with mean value 9.38 (+ 1.03) cm. Weight ranged from 150 to 394 gm with mean value 235.92 (+ 41.72) gm. Length of the heart showed a non-significant positive correlation with the age of an individual but a significant positive correlation with the height. Key words: Heart; Age; Height DOI: 10.3329/bja.v7i2.6087 Bangladesh J. Anat. 2009; 7(2) : 80-83